How to Make Them Hear: Challenging International Oil Interests in Ecuador’s Amazon Region - Rogge, Malcolm (Refuge: Canada’s Journal on Refugees, 1997)
This article discusses how oil development in the Amazon basin of Ecuador threatens to displace indigenous peoples through environmental contamination and colonization. It presents approaches to capacity-building for indigenous and mestizo-settler communities to deal with threats to human rights and the environment due to oil development. While the focus is on transnational oil operations in the Ecuadorian Oriente, many of the issues and empowerment methods discussed here are transferable to other local/global conflicts around the world, especially where indigenous and peasant communities are adversely affected by transnational resource extraction activities (mining, forestry, and oil).